Edukasi Kesehatan Reproduksi Remaja Putri dan Pembentukan Kader Remaja Sehat Reproduksi - Meinarisa Meinarisa; Riska Amalya Nasution; Kamariyah Kamariyah; Khairul Alim (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This community service aims to increase young women's knowledge and form a cadre of reproductively healthy teenagers. The method for implementing this service was counseling and FGD. The evaluation instrument used the adolescent menstrual attitude questionnaire, which was analyzed descriptively. The results of this service showed that there had been significant changes in young women's knowledge regarding reproductive health and attitudes towards maintaining reproductive health during menstruation and the environment. This result was proven by pretest-posttest data on the knowledge and attitudes of young women in maintaining personal and environmental hygiene during menstruation. Apart from that, reproductive health cadres had been formed to support school activities and personal hygiene for young women. These cadres were volunteers and provided their peers with information related to reproductive health to their peers.